Given. Volume 1 - Kizu, Natsuki, 1992- (Given, 2020)
"Love of music unites the four members of the band Given: hot headed guitarist Uenoyama, playboy drummer Akihiko, gentle bassist Haruki, and Mafuyu, a singer gifted with great talent and burdened by past tragedy. Their struggles and conflicts may drive them apart, but their band to the music, and to one another, always brings them back together again. Ritsuka Uenoyama is bored with it all--with school, with his basketball club, and even with his one true passion: playing guitar. That is, until the day he finds his favorite hidden napping spot occupied by a strange boy cradling a broken-stringed guitar. At first, Uenoyama is nonplussed by Mafuyu Sato and his slightly odd behavior, but when on a whim, he asks Mafuyu to sing, the power of that song pierces him to the core."--Provided by publisher